The effect of Concentration and Application Method of Potato Starch Edible Coating on the Quality of Tomatoes - Ramadani, Rifani; Syah, Ryan Firman; Kristalisasi, Elizabeth Nanik (Jurnal Biologi Tropis, 2025)
Tomatoes are a perishable commodity meaning they are prone to spoilage and physiological damage after harvest can affect their shelf life, solution to address this issue is by using coating. This study aims to determine how the interaction between concentration and application method of potato starch edible coating affects the results and to find the best concentration and application method of the potato starch edible coating. The research was conducted at the central laboratory of the Instiper campus in Maguwoharjo, Sleman District, Yogyakarta. A Completely Randomized Design (CRD) with two factors was used in this study. The first factor is the concentration of the edible coating solution, which consists of 5 levels (control, 2.5%, 5%, 7.5%, and 10%). The second factor is the application method of the potato starch edible coating, which consists of 3 levels (dipping, spraying, and brushing), each with 3 replications. The data obtained were then analyzed using Analysis of Variance (ANOVA) at a 5% significance level. If significant differences were found, further tests were performed using Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that there is an interaction between the concentration and application method of the potato starch edible coating on the vitamin C content and texture of the tomatoes. Tomatoes coated with 5% potato starch edible coating showed the best results in terms of vitamin C content and texture, and the application method of the edible coating produced similar results when compared to dipping in terms of tomato color.